Genotypic resistance testing improves antiretroviral treatment outcomes in a cohort of adolescents in Cameroon: Implications in the dolutegravir‑era - Willy L.R.T. Pabo; Debimeh Njume; Roland N. Ndip; Desiré Takou; Maria-Mercedes Santoro; Collins Chenwi; Grace Beloumou; Ezechiel N.J. Semengue; Alex D. Nka; Aude C. Ka'e; Georges Teto; Beatrice Dambaya; et al. (AOSIS, 2023)
Poor internet infrastructure limits the use of computer-based nursing process forms in rural areas. This study aimed to configure a computer‑based nursing process form to support nursing diagnosis and care evaluation in rural healthcare clinics in Africa. This study utilized a methodological design. The design process utilized a three-stage procedure involving planning, configuration, and testing. Seven faculty members volunteered to participate in the laboratory verification process. Each simulation session lasted 45 min and span from patient admission to exit. The experts independently scored the software functionality dichotomously as Not Suitable (score 0) and Suitable (score 1) for nursing practice. The agreement between the faculty volunteers was 0.857. The configuration of a readily available Microsoft Access computer application to support nursing diagnosis without internet service is possible. Health facilities in rural areas without internet connectivity should resort to such local configurations to maximize the benefits of electronic‑based documentation.